2019
DOI: 10.3390/su12010199
|View full text |Cite
|
Sign up to set email alerts
|

Weather Uncertainty and Efficacy of Fumigation in Tomato Production

Abstract: This study quantifies the effect of weather factors on fumigation efficacy in terms of weed control, tomato yield, and the overall economic performance of fumigants. High soil temperature was found to reduce the efficacy of all fumigants against nutsedge, while rainfall only reduced the efficacy of a limited number of fumigants. The fumigants’ economic performance over a range of weather conditions was further simulated to identify the fumigant that is most effective under diverse weather conditions. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…As foreign competition and domestic challenges such as labor shortages (Bampasidou and Salassi, 2019;Beal Cohen et al, 2020;Guan et al, 2015;Roka and Guan, 2018) and the phase-out of methyl bromide (Cao et al, 2019;Wu et al, 2020) increasingly erode the profitability of US growers, solutions must be found to make the industry viable and competitive. This applies not only to the fresh tomato industry but also to other major fresh produce commodities such as peppers (Biswas et al, 2018) and berries (Suh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As foreign competition and domestic challenges such as labor shortages (Bampasidou and Salassi, 2019;Beal Cohen et al, 2020;Guan et al, 2015;Roka and Guan, 2018) and the phase-out of methyl bromide (Cao et al, 2019;Wu et al, 2020) increasingly erode the profitability of US growers, solutions must be found to make the industry viable and competitive. This applies not only to the fresh tomato industry but also to other major fresh produce commodities such as peppers (Biswas et al, 2018) and berries (Suh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Weather conditions affect fumigant efficacy. Wu et al 59 used empirical models to study the effect of weather conditions on fumigants for weed control and found that high soil temperature reduced the efficacy of a number of soil fumigants, including 1,3-D + Pic, 1,3-D + Pic + metam potassium, methyl bromide + Pic, and DMDS + Pic, against purple nutsedge. In the present study, the variability in fumigant efficacy between years was greater for 1,3-D + Pic, while less evident for DMDS + metam potassium.…”
Section: Discussionmentioning
confidence: 99%
“…Our survey verified the widespread adoption of fumigants as a critical component of integrated weed management (IWM) programs for intensive strawberry production systems in Florida. However, fumigant efficacy on weeds is often variable (Khatri et al 2021a;Wu et al 2020), though there is strong evidence that fumigants kill weed seeds (Khatri et al 2021b;Klose et al 2008). Field trials are needed to evaluate the long-term impacts of fumigants on weed population dynamics.…”
Section: General Productionmentioning
confidence: 99%